2023
DOI: 10.1021/acs.jcim.2c01504
|View full text |Cite
|
Sign up to set email alerts
|

Vina-GPU 2.0: Further Accelerating AutoDock Vina and Its Derivatives with Graphics Processing Units

Abstract: Modern drug discovery typically faces large virtual screens from huge compound databases where multiple docking tools are involved for meeting various real scenes or improving the precision of virtual screens. Among these tools, AutoDock Vina and its numerous derivatives are the most popular and have become the standard pipeline for molecular docking in modern drug discovery. Our recent Vina-GPU method realized 14-fold acceleration against AutoDock Vina on a piece of NVIDIA RTX 3090 GPU in one virtual screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…For stage 1, we first generate 36 pocket conformations using the empty pocket packing model given the pocket backbone conformation, then calculate the RMSD matrix and cluster them into 6 groups using the K-Medoids algorithm, and then use the medoids of each cluster as the representative conformation, thus simulating the conformation selection theory. After obtaining 6 pocket conformations similar to the “free” state, we dock one ligand conformation for each of them using Vina -GPU [67] (for work efficiency, the docking process uniformly uses GPU-accelerated Vina ). For stage 2, we use the ligand induced pocket packing model with the 6 ligand conformations obtained in the stage 1 as the initial condition.…”
Section: Methodsmentioning
confidence: 99%
“…For stage 1, we first generate 36 pocket conformations using the empty pocket packing model given the pocket backbone conformation, then calculate the RMSD matrix and cluster them into 6 groups using the K-Medoids algorithm, and then use the medoids of each cluster as the representative conformation, thus simulating the conformation selection theory. After obtaining 6 pocket conformations similar to the “free” state, we dock one ligand conformation for each of them using Vina -GPU [67] (for work efficiency, the docking process uniformly uses GPU-accelerated Vina ). For stage 2, we use the ligand induced pocket packing model with the 6 ligand conformations obtained in the stage 1 as the initial condition.…”
Section: Methodsmentioning
confidence: 99%
“…The computational time is also crucial to deciding which docking program to choose for virtual screening purposes. Recently, Autodock Vina has been modified to fit the GPU architecture, which significantly accelerates the computations and adds more advantages in comparison to other molecular docking software [48].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, molecular docking tools provide an efficient and cost-effective means for the initial stages of drug design, allowing the identification of potential compounds and the evaluation of their binding affinities [2], [3], [4]. Among the available tools, the AutoDock Vina suite and its derivatives are widely regarded as the preferred choice for molecular docking, owing to their remarkable speed and accuracy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have revealed that early iterations of AutoDock Vina and its derivatives are incapable of meeting the speed requirements imposed by contemporary drug discovery practices, necessitating the development of accelerated versions [5], [6]. Graphics Processing Units (GPUs) have emerged as an ideal solution for common users due to their accessibility, cost-effectiveness, and ease of implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation